The Theory of Physical Particles and Yi Field. - Cong, Qiu-zi (Cambridge Scholars Publisher, 2021)
This book integrates the research achievements of both western natural sciences and the traditional oriental idea of Yi into a 'Five-Element Theory of Li Yin and Yang'. By forming the Liyi time-space concept of the theory of quaternions, it proposes four fundamental principles on the basis of the mass-energy-time-space four-image principle. Utilizing the mathematical time-space principle and basic calculus methods, the theory depicts the so-called principles and rules as a simple mathematical model that can be used to comprehend the basic concepts of dynamics, such as matter, motion, time-spac.